Bacterial effector targeting of a plant iron sensor facilitates iron acquisition and pathogen colonization. Issue 6 (5th March 2021) - Xing, Yingying; Xu, Ning; Bhandari, Deepak D; Lapin, Dmitry; Sun, Xinhua; Luo, Xuming; Wang, Yeqiong; Cao, Jidong; Wang, Hongbin; Coaker, Gitta; Parker, Jane E; Liu, Jun
Abstract: Acquisition of nutrients from different species is necessary for pathogen colonization. Iron is an essential mineral nutrient for nearly all organisms, but little is known about how pathogens manipulate plant hosts to acquire iron. Here, we report that AvrRps4, an effector protein delivered by Pseudomonas syringa e bacteria to plants, interacts with and targets the plant iron sensor protein BRUTUS (BTS) to facilitate iron uptake and pathogen proliferation in Arabidopsis thaliana . Infection of rps4 and eds1 by P. syringae pv. tomato ( Pst ) DC3000 expressing AvrRps4 resulted in iron accumulation, especially in the plant apoplast. AvrRps4 alleviates BTS-mediated degradation of bHLH115 and ILR3(IAA-Leucine resistant 3), two iron regulatory proteins. In addition, BTS is important for accumulating immune proteins Enhanced Disease Susceptibility1 (EDS1) at both the transcriptional and protein levels upon Pst ( avrRps4 ) infections. Our findings suggest that AvrRps4 targets BTS to facilitate iron accumulation and BTS contributes to RPS4/EDS1-mediated immune responses. Abstract : The bacterial pathogen Pseudomonas syringae secretes an effector protein, AvrRps4, that facilitates colonization by manipulating iron homeostasis in Arabidopsis plants.